1991
DOI: 10.1055/s-1991-26431
|View full text |Cite
|
Sign up to set email alerts
|

Titanium(IV) Isopropoxide-Catalyzed Formation of 1-Substituted Cyclopropanols in the Reaction of Ethylmagnesium Bromide with Methyl Alkanecarboxylates

Abstract: Titanium(IV) Isopropoxide-Catalyzed Formation of 1-Substituted Cyclopropanols in the Reaction of Ethylmagnesium Bromide with Methyl Alkanecarboxylates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
129
0
5

Year Published

1998
1998
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 278 publications
(134 citation statements)
references
References 0 publications
0
129
0
5
Order By: Relevance
“…The observation that an additional equivalent of the Grignard reagent was necessary in the noncatalytic reaction to achieve good yields of cyclopropanols, together with a similar finding in the reaction of titanacyclopropane 1 with allylic alcohol derivatives, [19] led to the proposal [20] that addition of a Grignard reagent to complex 10 initiates the formation of the carbonϪcarbon bond to give the titanacyclopentane complex 14 (Scheme 6). Fragmentation of the latter affords the β-oxotitanium derivative 15, which ring-closes to titanium cyclopropanolate 16, which, as in the first proposed mechanism, [5,6] further transforms into the diethyltitanium derivative 8 and magnesium cyclopropanolate 13. If the alkoxide group at the titanium atom is considered to be a 6e ligand, it can be concluded that the complex 14 and the titanacyclopropaneϪester complex 10 are 18e organometallic species, whereas oxatitanacyclopentane 11 is a 16e organometallic species.…”
Section: Generation Of Dialkoxytitanacyclopropanes From Dialkyltitanimentioning
confidence: 78%
See 2 more Smart Citations
“…The observation that an additional equivalent of the Grignard reagent was necessary in the noncatalytic reaction to achieve good yields of cyclopropanols, together with a similar finding in the reaction of titanacyclopropane 1 with allylic alcohol derivatives, [19] led to the proposal [20] that addition of a Grignard reagent to complex 10 initiates the formation of the carbonϪcarbon bond to give the titanacyclopentane complex 14 (Scheme 6). Fragmentation of the latter affords the β-oxotitanium derivative 15, which ring-closes to titanium cyclopropanolate 16, which, as in the first proposed mechanism, [5,6] further transforms into the diethyltitanium derivative 8 and magnesium cyclopropanolate 13. If the alkoxide group at the titanium atom is considered to be a 6e ligand, it can be concluded that the complex 14 and the titanacyclopropaneϪester complex 10 are 18e organometallic species, whereas oxatitanacyclopentane 11 is a 16e organometallic species.…”
Section: Generation Of Dialkoxytitanacyclopropanes From Dialkyltitanimentioning
confidence: 78%
“…[4,5] We found that the interaction of ethylmagnesium bromide with isopropoxytitanium butyrate (6), which was being studied as a model ZeiglerϪNatta process, results in the formation of 1-propylcyclopropanol (7) (Scheme 3). [5] Although the latter was ob- tained as a minor product in low yield, our experience in the chemistry of cyclopropanes [17,18] allowed us to foresee the considerable potential of this unusual reaction and impelled us to investigate the reaction systematically.…”
Section: Generation Of Dialkoxytitanacyclopropanes From Dialkyltitanimentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction of unsaturated esters, [4] amides, [5] imides, [6] and related compounds [7] with an alkene ± titanium complex [8] is a very convenient method to prepare bicyclic cyclopropanols [4] and cyclopropylamines [5] in one step [Eqs. (1) and (2); X R'O, Cl, Br].…”
mentioning
confidence: 99%
“…The molar ratio of H introduced to WO 2À 4 is defined as the degree of acidification of the metalate solution, the molar ratio of H that reacted per WO 2À 4 is the degree of protonation. [8] …”
mentioning
confidence: 99%